Guaranteeing russia’s responsibility for war crimes in Ukraine: the information and legal aspect - О. Ya. Kovalchuk (Bulletin of Kharkiv National University of Internal Affairs)
The article examines the issue of bringing russia to justice for mass war crimes, crimes against humanity and acts of aggression committed during the full-scale invasion of Ukraine. The purpose of the work is to analyse the available legal instruments, to formulate a comprehensive approach to solving this problem and to search for effective information and legal mechanisms to ensure the inevitability of russia's punishment under international law.